Gender differences among newly diagnosed type 2 diabetes mellitus patients at tertiary care hospital - Verma K; Karnam N; Haritha M; Manchi RK; Sangeeta BSR (Journal of Medical and Scientific Research)
Background: Diabetes mellitus (DM) refers to a diverse group of metabolic conditions marked by elevated blood sugar levels, with type 2 DM specifically involving insulin resistance where cells fail to respond effectively to insulin. The objective of the study was to evaluate gender differences among type 2 diabetes mellitus (T2DM) patients based on body mass index (BMI), clinical presentation and glycemic parameters.